Noradrenalin and dopamine receptors both control cAMP-PKA signaling throughout the cerebral cortex - Nomura, Shinobu; Bouhadana, Maud; Morel, Carole; Faure, Philippe; Cauli, Bruno; Lambolez, Bertrand; Hepp, Régine (Frontiers in Cellular Neuroscience, 2014)
Noradrenergic fibers innervate the entire cerebral cortex, whereas the cortical distribution of dopaminergic fibers is more restricted. However, the relative functional impact of noradrenalin and dopamine receptors in various cortical regions is largely unknown. Using a specific genetic label, we first confirmed that noradrenergic fibers innervate the entire cortex whereas dopaminergic fibers were present in all layers of restricted medial and lateral areas but only in deep layers of other areas. Imaging of a genetically-encoded sensor revealed that noradrenalin and dopamine widely activate PKA in cortical pyramidal neurons of frontal, parietal and occipital regions with scarce dopaminergic fibers. Responses to noradrenalin had higher amplitude, velocity and occurred at more than 10 fold lower dose than those elicited by dopamine, whose amplitude and velocity increased along the antero-posterior axis. The pharmacology of these responses was consistent with the involvement of Gs-coupled beta1 adrenergic and D1/D5 dopaminergic receptors, but the inhibition of both noradrenalin and dopamine responses by beta adrenergic antagonists was suggestive of the existence of beta1- D1/D5 heteromeric receptors. Responses also involved Gi-coupled alpha2 adrenergic and D2- like dopaminergic receptors that markedly reduced their amplitude and velocity and contributed to their cell-to-cell heterogeneity. Our results reveal that noradrenalin and dopamine receptors both control cAMP-PKA signaling throughout the cerebral cortex with moderate regional and laminar differences. These receptors can thus mediate widespread effects of both catecholamines, which are reportedly co-released by cortical noradrenergic fibers beyond the territory of dopaminergic fibers.